2003
DOI: 10.1046/j.1365-2133.2003.05408.x
|View full text |Cite
|
Sign up to set email alerts
|

Dry environment increases mast cell number and histamine content in dermis in hairless mice

Abstract: These results suggest that a low environmental humidity increases mast cell number and dermal histamine content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 38 publications
3
61
0
2
Order By: Relevance
“…For example, it stimulates epidermal DNA synthesis and amplifies the hyperproliferative response to barrier disruption (2), increases IL-1a in epidermis (3) and increases histamine and mast cells in dermis (4). Allergic response is also enhanced by environmental dryness (5).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it stimulates epidermal DNA synthesis and amplifies the hyperproliferative response to barrier disruption (2), increases IL-1a in epidermis (3) and increases histamine and mast cells in dermis (4). Allergic response is also enhanced by environmental dryness (5).…”
Section: Introductionmentioning
confidence: 99%
“…Denda et al [51] and his colleagues at Shiseido [52] have also demonstrated that exposure to a dry environment directly increased epidermal interleukin 1 levels and that the increased level of this cytokine is greater on experimentally challenging the barrier. More recently, the same group has also reported increased numbers of mast cells and increased dermal but not epidermal histamine levels [53] . Others have reported increased SC nerve growth factor levels [54] and increased C fi bres in dry skin elicited by dry environments [55] .…”
Section: The Effect Of Environmental Atmospheric Conditions On Epidermentioning
confidence: 97%
“…On the other hand, a drastic decrease of environmental humidity induced barrier abnormality [ 95 ] , and a decrease in the water retention capacity of the stratum corneum [ 67 ] . Ashida et al demonstrated an increase of IL-1 a in the epidermis [ 4 ] and an increase of histamine and mast cells in the dermis [ 3 ] in a dry environment. Hosoi et al demonstrated that the allergic response was enhanced by low environmental humidity [ 55 ] .…”
Section: Humiditymentioning
confidence: 99%